Antimicrobial resistance of Pasteurella multocida strains isolated from pigs between 2010 and 2016. Issue 1 (31st July 2018) - Oh, Yoon‐Hee; Moon, Dong‐Chan; Lee, Young Ju; Hyun, Bang‐Hun; Lim, Suk‐Kyung
Abstract : Pasteurella multocida is one of the significant causes of respiratory infection outbreaks in the Korean pig industry. Although antimicrobial treatment is an effective strategy for controlling respiratory diseases, limited information is available regarding the antimicrobial susceptibility of the pathogens infecting Korean pigs. Therefore, in this study, we evaluated the antimicrobial resistance of P multocida against widely used antimicrobials in order to enable the selection of appropriate drugs and to evaluate any trends in resistance. A total of 454 isolates of P multocida were collected from all provinces in Korea between 2010 and 2016. Antimicrobial susceptibility of all isolates was determined using a broth microdilution method. The most frequently observed resistance was to sulphadimethoxine (76.0 per cent), followed by oxytetracycline (66.5 per cent), chlortetracycline (36.8 per cent) and florfenicol (18.5 per cent). Although no consistent increase or decrease in resistance was observed for most antimicrobials, resistance to fluoroquinolones tended to increase over the study period. A variety of resistance patterns were observed, most frequently for tetracyclines and sulphonamides. These findings could provide information enabling the selection of optimal antimicrobials for efficient treatment of pneumoniae pasteurellosis in pig farms, which would impede the emergence of antimicrobial resistance.